Stakeholder Perspectives on Sustainability in the Food-Energy-Water Nexus - Bielicki, Jeffrey M.; Beetstra, Margaret A.; Kast, Jeffrey B.; Wang, Yaoping; Tang, Shaohui (Frontiers in Environmental Science, 2019)
Interest in the various dimensions of environmental, economic, and social sustainability for food, energy, and water (FEW) systems, independently and collectively (i.e., the FEW nexus), has spawned an increasing amount of literature that seeks to understand the various linkages within the FEW nexus and provide guidance to inform decision-making to enhance sustainability. While the use of science and data can generate important and relevant information, it is not clear how important they are relative to relevant policy and the integration of policy within and across the individual FEW domains. In this work, we assessed perspectives on various considerations that pertain to sustainability in the FEW nexus. To do so, we identified numerous stakeholder groups who have interests throughout the FEW nexus, and conducted a survey of a subset of these groups. Although the responses differed across the stakeholder groups that we surveyed, the consistent result was that stakeholders generally understand that FEW systems are physically connected at high levels, and that policy is less integrated than desired. When forced to choose between priorities for science and data or for integrated policy to enhance sustainability, respondents from Academia and Extension preferred more science and data, whereas respondents who are, or more frequently interact with, practitioners and policy-makers preferred integrated policy. Overall, with other results and findings that are relevant for advancing sustainability and improving communication the FEW nexus, we conclude that the importance of science, data, and integrated policy depends on the context in which the stakeholders operate in the FEW domain.